Aldosterone Synthase CYP11B2 Gene Promoter Polymorphism in a Turkish Population With Chronic Kidney Disease (Iranian Journal of Kidney Diseases, 2015)
Introduction. It has been shown that gene polymorphisms influence the development and progression of chronic kidney disease (CKD). Many studies have indicated that aldosterone synthase CYP11B2 gene polymorphism (-344C>T) influences the aldosterone level, urinary aldosterone excretion, blood pressure, and left ventricular size and mass. We aimed to investigate whether there is an effect of CYP11B2 -344 C>T polymorphism on the development of CKD in a Turkish population. Material and Methods. A total of 240 patients with stage 5 CKD and 240 age- and sex-matched healthy individuals were included in the study. Genotyping of CYP11B2 gene -344 T>C promoter polymorphism was carried out using polymerase chain reaction and restriction fragment length polymorphism methods. Results. No significant differences were found in the genotype distribution of CYP11B2 -344 C>T polymorphism between the patients and controls; however, -344 C>T polymorphism was significantly more frequent among the CKD patients with diabetes mellitus as compared to those with it (P = .02). Diabetic CKD patients with TC genotype had a 2-fold increased risk for development of the disease than the CKD patients without diabetes mellitus (odds ratio, 2.21; 95% confidence interval, 1.04 to 4.67). Conclusions. Our study suggests that the CYP11B2 gene -344 C>T polymorphism may have an effect on the development of CKD in diabetic patients.